A política regulatória contemporânea dos regimes de previdência do funcionalismo público no Brasil: Avanços, limitaç\~oes e propostas - Fernando Ferreira Calazans; Marcelo Abi-Ramia Caetano (Instituto de Pesquisa Econômica Aplicada (IPEA), 2013)
– This paper analyses the regulation on public pensions created by the Law 9.717/1998 and the Constitutional Amendment 20/1998 and the current reality on public pension's regulation. It has been verified that public pensions demand a management that should be efficient, transparent, and democratic and should focuses on the actuarial and financial equilibrium. We propose the creation of regulation instruments which aims at the dissemination of information, auto regulation and social control which could complement the running mechanisms of incentives and disincentives promoted by the federal government due to the great quantity of public pension's schemes and the dimension of the Brazilian territory.
Keywords: H77; H83; H55; 330; pensions; public service; auto regulation; social participation